Treffen des Escherbundes in Elm 1941 (oder 1944), Fritz Baumann
politischer Rahmen;politisches Leben (allgemein);politische Bewegung;soziale Bewegung politischer Rahmen;politisches Leben (allgemein);politische Ideologie;Sozialismus